2009
DOI: 10.1002/uog.6304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a low‐lying placenta on delivery outcome

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 6 publications
1
43
0
Order By: Relevance
“…Vergani and colleagues reported that more than two thirds of women with placental edge and os distance >1 cm and 1-2 cm within 4 weeks of delivery according to Bronsteen had successful vaginal delivery. 19,20 In our case, only one had normal successful vaginal delivery.…”
Section: Discussionmentioning
confidence: 53%
“…Vergani and colleagues reported that more than two thirds of women with placental edge and os distance >1 cm and 1-2 cm within 4 weeks of delivery according to Bronsteen had successful vaginal delivery. 19,20 In our case, only one had normal successful vaginal delivery.…”
Section: Discussionmentioning
confidence: 53%
“…25,26 Conversely, if there is less than 1 cm between the edge of the placenta and the os, the chances of hemorrhage are so high as to warrant planned cesarean delivery. 26,27 The optimal management of patients with between 1.0 and 2.0 cm between the os and the placenta is uncertain (Fig. 3).…”
Section: Managementmentioning
confidence: 99%
“…As compared to those with cervical os to placental edge distance between 11-20 mm, patients with internal cervical os to placental edge distance 10 mm have high rates of antepartum hemorrhage (29% vs 3%; odds ratio, 11.5; 95% confidence interval, 1.6e76.7) 13 and cesarean delivery rates 73-91% vs 24-40%. 10,13,14 However, there are no significant differences in the gestational ages at delivery between the 2 groups and 75-80% of these patients are delivered at term. 13 The thickness of the lower placental edge has also been evaluated as a predictor of bleeding in patients with marginal/low-lying placentas.…”
Section: Marginal/low-lying Placentamentioning
confidence: 79%
“…20 In women with low-lying placenta (cervical os to placental edge distance 20 mm), cervical length has been studied as a predictor of antepartum bleeding and indicated preterm birth. 10,[12][13][14] It was found that short cervix ( 25 mm) was associated with higher rates of antepartum bleeding (75% vs 31%; P ¼ .02), blood transfusion (25% vs 3%; P ¼ .02), lower birthweight (62% vs 17%; P ¼ .02), and neonatal intensive care unit admissions (50% vs 17%; P ¼ .04). 22 Figure 3 is a proposed guideline for managing asymptomatic patients with marginal or low-lying placenta based on published literature that has used internal cervical os to placental edge distance cutoffs of <1, 1-2, and >2 cm; placental edge thickness cutoff of 1 cm; and cervical length cutoff of 25 mm.…”
Section: Marginal/low-lying Placentamentioning
confidence: 95%
See 1 more Smart Citation